Analysis of the role of online transportation on tourism development (A study of tourists on users of grab online transportation services in kupang city) - Yehezkiel Bora; Rolland E. Fanggidae; Apriana H. J. Fanggidae (Review of Multidisciplinary Academic and Practice Studies, 2025)
Purpose: The purpose of this study is to analyze whether the existence of online grab transportation in Kupang City has a positive impact on tourism development, in this study using interview techniques. Research Methodology: The interview used was an unstructured interview, namely an independent interview in which the researcher did not use an interview guide that had been systematically structured. The sample in this study amounted to 15 respondents. The sampling technique used was random sampling. The data analysis technique used in this study is an interactive technique. Interactive technique is a data analysis technique that is carried out while in the field and after being in the field which is processed through four stages. Results: The results of this study indicate that the presence of online transportation (Grab) in Kupang City can actually be used as a means of promotion and transportation that is comfortable and safe, as well as practical and efficient. Comfortable and safe from the condition of the vehicle and the driver, as well as practical and efficient from the operation of the application and the ease of finding the driver so that it can save time by visiting all tourist objects in Kupang City.